Methodical recomendations for the organization of independent and individual extracurricular work of students "Histology of internal organs" - Sirtcov, V. K.; Sulaeva, O. N.; Aliyeva, E. G.; Zavgorodnyaya, M. I.; Makeyeva, L. V.; Zidrashko, G. A.; Pototskaya, E. I.; Сирцов, Вадим Кирилович; Сулаєва, Оксана Миколаївна; Алієва, Олена Геннадіївна; Завгородня, Марія Ігорівна; Макєєва, Людмила Валеріївна; et al. (ЗДМУ, 2016)
This manual is intended for the organization of independent and individual extracurricular work of medical students studying in English.
Keywords: histology; internal organs